Experiencias de maternidad en mujeres peruanas adultas que fueron madres en su adolescencia - del Carmen Robles-Esparza, Andrea (2022)
Abstract-The plastics industry is important in the world due to its recurrent use in daily life and the supply it provides to other sectors such as medicine, transportation, health. Previous studies show that the average difference in global efficiency between the manufacturing industry and the World Class ranges between 15 to 25 percentage points, also affecting the plastics sector. The case study presents a gap of 17% regarding this metric in the thermoforming line. This efficiency gap has had an impact on cancelled orders, which generate 18.8% of annual sales losses. During the analysis it was determined that availability losses are generated by constant machinery breakdowns and quality losses are caused by the high rate of nonconforming products. Thus, in view of the scarcity of efforts in the sector, an efficiency maximization model is proposed that combines the management of time and machinery with the quality associated with the process. To this end, the integration of tools such as 5S, autonomous and planned maintenance to reduce unscheduled stops and standardization under a continuous improvement framework to reduce the sources of quality loss is proposed. In this way, an improvement of 12.15% in the efficiency of the line is achieved, increasing by 3.36% and 10.96% in the Availability and Quality indicators respectively for the M4 thermoforming machine.